Industrial safety and environment management (ISEM) - Anuar Ahmad; Zularisam Abd. Wahid (Penerbit Universiti Malaysia Pahang, 2011)
[This book] provides a theoretical and practical basis for the behavior and biological effects of natural chemical entities and contaminants in natural systems, concluding with a practical focus on risk assessment and the environmental management of chemicals